PSYCHOLOGICAL ASPECTS OF THE FORMATION OF MORAL CONSCIOUSNESS IN STUDENTS (American Journal of Research in Humanities and Social Sciences, 2024)
In the article there is considered the issue of moral ideas of students during their study in higher education institution